A noninflammatory mRNA vaccine for treatment of experimental autoimmune encephalomyelitis - Krienke, Christina; Kolb, Laura; Diken, Elif; Streuber, Michael; Kirchhoff, Sarah; Bukur, Thomas; Akilli-Öztürk, Özlem; Kranz, Lena M; Berger, Hendrik; Petschenka, Jutta; Diken, Mustafa; Kreiter, Sebastian; et al. (Science (American Association for the Advancement of Science), 2021)
The ability to control autoreactive T cells without inducing systemic immune suppression is the major goal for treatment of autoimmune diseases. The key challenge is the safe and efficient delivery of pharmaceutically well-defined antigens in a noninflammatory context. Here, we show that systemic delivery of nanoparticle-formulated 1 methylpseudouridine-modified messenger RNA (m1Ψ mRNA) coding for disease-related autoantigens results in antigen presentation on splenic CD11c antigen-presenting cells in the absence of costimulatory signals. In several mouse models of multiple sclerosis, the disease is suppressed by treatment with such m1Ψ mRNA. The treatment effect is associated with a reduction of effector T cells and the development of regulatory T cell (T cell) populations. Notably, these T cells execute strong bystander immunosuppression and thus improve disease induced by cognate and noncognate autoantigens.